PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI, SISTEM PELAPORAN DAN KETAATAN PERATURAN PERUNDANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi Empiris Pada OPD Di Indragiri Hilir) - Shara Carolina; Yesi Mutia Basri; Julita Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The purpose of this research is to determine the effect of budget goal clarity,control of accounting, reporting systems and the adherence of the law regulationon the performance accountability of government performance. The samplingtechnique used purposive sampling. The method of collecting data throughquestionnaires was given directly to the head of office staff, head of subdivisionand finance of the planning subdivision in all Regional OrganizationOrganizations (OPD) in the Indragiri Hilir Regency Government. The dataobtained were analyzed using the Statistical Package for Social Sciences (SPSS)through SPSS 25 software. The results of empirical studies show that (1) budgetgoal clarity had a significant and possitive affect to performance accountability ofgovernment performance with a significance value of 0.008 <0.05, (2) control ofaccounting had a significant and possitive affect to performance accountability ofgovernment performance with a significance value of 0,015<0,05, (3) reportingsystems had not significantly but possitive affect to performance accountability ofgovernment performance with a significance value of 0,005<0,05 (4) theadherence of the law regulation had not significantly but possitive affect toperformance accountability of government performance with a significance valueof 0,836<0,05.KeyWords : budget goal clarity, control of accounting, reporting systems, theadherence of the law regulation, the performance accountability ofgovernment performance.